The Effect of Digital Marketing, Online Customer Reviews and Ratings on Consumer Buying Interest Through Shopee - Gina Alivea Oryza; Sengguruh Nilowardono (Jurnal Ekonomi, 2022)
This study aims to analyze the effect of digital marketing, online customer review rating on consumer buying interest through shopee. The analytical method used in this study is quantitative analysis by conducting a survey on 106 respondents, namely students from Narotama University who have made purchases through shopee and tested with the help of an analytical tool, namely the SPSS program. The results of this study indicate that digital marketing, online customer reviews and ratings have a positive effect on buying interest through shopee. When consumers feel that shopee's digital marketing is attractive, online customer reviews and other user ratings provide benefits in terms of providing product-related information, this can increase purchase intention.